Seven novel MHC class I alleles identified in Cercopithecus mitis. Issue 6 (27th March 2014) - Liu, B.; Yan, X.; Fan, J. W.; Zeng, L.; Sun, Z. Z.
<x xml:space="preserve">Abstract</x> We report here the identification of three Cemi‐A and four Cemi‐B novel alleles of Cercopithecus mitis.